THE INFLUENCE OF FAMILY COUNSELING WITH A CONJOINT APPROACH ON THE ROLE OF THE FAMILY IN THE MANAGEMENT OF PEOPLE WITH DIABETES MELLITUS IN THE WORK AREA OF THE BOJONGMANIK INPATIENT HEALTH CENTER - Novelia, Hera; Barkah, Asep (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Diabetes is a metabolic disease that arises due to high levels of sugar in the body and its use is not optimal. Diabetes is classified as a dangerous chronic category of disease, especially when it has reached complications. Purpose: To determine the effect of counseling carried out on families using a conjoint approach to the role of families in the management of DM sufferers in the work area of the Bojongmanik Inpatient Health Center. Methods: This study applies a pre-experimental research design. This research design uses one group pretest-posttest, which is a measure of the pretest size given to respondents. The location of the study was conducted at the Bojongmanik Inpatient Health Center, Lebak Regency. The number of samples in this study was 21 respondents. Results: Based on the calculation method carried out with the Wilcoxon sign rank test, the values obtained are: negative ranks mean rank value and the sum of ranks is 0, meaning that there are no samples/respondents who have a post-test value lower than the pre-test value, all samples (21 respondents) have a higher post-test value than the pre-test value. Referring to the calculation results of the Wilcoxon signed ranks test, the Z value obtained is -4.048 with a p-value (Asymp Sig 2-tailed) of 0.000 where the value is less than 0.05. Conclusion: Researchers concluded that there is an influence of family counseling conducted which can be seen from several analysis results. The results of the Wilcoxon test conducted obtained a Z value of -4.048 with a p-value (Asymp Sig 2 tailed) of 0.000 where the value was less than 0.05.